IMPROVING THE PREVENTION OF OBESITY AMONG THE POPULATION (The New Uzbekistan Journal of Medicine, 2025)
Preventing obesity in the population is one of the pressing issues of the healthcare system. An integrated approach to obesity prevention includes promoting a healthy lifestyle, fostering nutritional awareness, and encouraging physical activity. This article explores ways to improve obesity prevention, focusing on healthy eating programs, educational training, and effective methods for informing the population.